The Case Study of Pseudoexcitation Method Combining Self-Adaptive Gauss Integration in Random Vibration Analysis - Chen, Ning; Li, Yongle; Zhu, Siyu (Shock and vibration, 2019)
The pseudoexcitation method (PEM) can improve efficiency of random vibration analysis. However, for large-sized structures with wide frequency range of response, the workload of calculation is heavy if conventional integration methods, such as trapezoidal integration, are used to combine with the PEM to calculate structural response. In such case, self-adaptive technology is induced to combine with the PEM to form an efficient method for solving random vibration. During calculation, this method can realize the adaptability of random excitation to actual structural response, identify automatically critical frequency intervals of random excitation, and process intelligently the identified critical frequency intervals and noncritical frequency intervals. Based on the identified frequency intervals, Gauss integration is carried out to obtain response results with random characteristics. The computational efficiency and accuracy of PEM-SGI are verified by wind-induced performance of the slender bridge tower. Finally, the influence of damping ratio of the bridge structure and train marshalling on vehicle-bridge coupled system is investigated to further verify the application of the proposed method. Results show that the efficiency of solving random vibration can be improved by the present method.